Geologia, química mineral e geocronologia das ocorrências de Fe-P tipo Kiruna (IOA) no domínio do arco magmático de Santa Quitéria, municípios de Ararendá e Ipaporanga/CE - Lino, Ramon de Oliveira (2019)
Recent occurrences of IOA (Iron Oxide-Apatite) IOA-type I-P- (Cu) were identified in the region of Ipaporanga / Ararendá, western edge of the magmatic arc in Santa Quitéria, associated to a range of metavulcanicas and albitized metadiorites, by biotite granite. The identification of the mineralized areas was optimized with the use of aerogeophysical images that showed the occurrences of iron associated with high magnetic and / or high K. Thus, two areas of occurrence (one in the northern sector and four in the southern sector) were recognized, totaling five types of ore: (1) magnetite-apatite ore tabular aspect composed from magnetite-titanic-tautaritic and or apatite composed exhibiting oxy-exolutions of ilmenite in trellis, with subordinate monazite, cut by post-collisional granite, which gives it an important phase of sulfidation (chalcopyrite and bornite); (2) isotropic magnetititic-apatite type, with and without specular hematite, fine granulation with magnetite aggregates and faceted apatite microcrystals; (3) protominério with magnetite disseminated in intrusion of hydrothermal diorite metaquartz, containing filaments with thickness between 0.5 and 3m, composed of magnetite, relicts of clinopyroxene; (4) massive hematite ore formed by hematite, euhedral and subhedral, with polisynthetic maclas, involving reliquies inclusions of deformed and martired magnetite; (5) occurrence of skarn with magnetite, granada, clinopyroxene and amphibole, in the form of loose blocks, probably developed under the influence of metadiorite rocks. The mineral chemistry data show, except for the occurrences in vein, F-rich apatite in all types of ore, and magnetite with different chemical compositions of magmatic affiliation associated or not with hydrothermal processes. The compositional difference between the different types of ore reflects more of a formation mechanism or complex history of mineralizations and metasomatic alterations, under the influence of liquids or fluids of different origins (eg magmatic fluids under the influence of the granite body, metamorphic and / or meteoric), common features in IOCG / Kiruna type mineralizer system. Analysis of U-Pb by ICP MS revealed ages of 554 ± 6 Ma for the metavulcanicas and 548 ± 4 Ma for the biotite granite, which shows a close genetic relationship between the two lithotypes. The proposed geodynamic evolution for the area depicts a post orogenic environment marked by shear, volcanic generation and plutonism. Iron occurrences have developed at various stages throughout geological time at different crustal levels. The discovery of these occurrences acquires significant geological and metallogenic importance, since there is no record of IOA type deposits in Brazil.